Clinical analysis of deceased donor liver transplantation in the treatment of hepatocellular carcinoma with segmental portal vein tumor thrombus: A long-term real-world study - Sha, Meng; Chen, Chen; Shen, Chuan; Jeong, Seogsong; Sun, Han-yong; Xu, Ning; Hang, Hua-lian; Cao, Jie; Tong, Ying (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) patients with portal vein tumor thrombus (PVTT) have conventionally been regarded as a contraindication for liver transplantation (LT). However, the outcomes of deceased donor liver transplantation (DDLT) in patients with segmental PVTT remain unknown. The aim of this study is to evaluate the feasibility and effectiveness of DDLT in the treatment of HCC with segmental PVTT. Methods: We retrospectively analyzed 254 patients who underwent DDLT for HCC in our institution from January 2015 to November 2019. To assess the risks of PVTT, various clinicopathological variables were evaluated. Overall (OS) and recurrence-free survival (RFS) analyses based on different PVTT types were performed in HCC patients. Results: Of the 254 patients, a total of 46 patients had PVTT, of whom 35 had lobar PVTT and 11 had segmental PVTT in second-order branches or below. Alpha-fetoprotein (AFP) level, tumor maximal diameter, histological grade, micro-vascular invasion (MVI), RFS, and OS were significantly different between the control and PVTT groups. Lobar PVTT was associated with unfavorable 5-year RFS and OS compared with MVI group (28.6% and 17.1%, respectively). Instead, no significant difference was observed between the segmental PVTT and MVI group in terms of 5-year RFS and OS (RFS: 36.4% vs. 40.4%, p=0.667; OS: 54.5% vs. 45.1%, p=0.395). Further subgroup analysis showed segmental PVTT with AFP levels ≤100 ng/ml presented significantly favorable RFS and OS rates than those with AFP level >100 ng/ml (p=0.050 and 0.035, respectively). Conclusions: In summary, lobar PVTT remains a contraindication to DDLT. HCC patients with segmental PVTT and AFP level ≤100 ng/ml may be acceptable candidates for DDLT.